1998
DOI: 10.1128/jvi.72.10.8453-8457.1998
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 as a Functional Coreceptor for Human Immunodeficiency Virus Type 1 Infection of Primary Macrophages

Abstract: The coreceptors used by primary syncytium-inducing (SI) human immunodeficiency virus type 1 isolates for infection of primary macrophages were investigated. SI strains using only CXCR4 replicated equally well in macrophages with or without CCR5 and were inhibited by several different ligands for CXCR4 including SDF-1 and bicyclam derivative AMD3100. SI strains that used a broad range of coreceptors including CCR3, CCR5, CCR8, CXCR4, and BONZO infected CCR5-deficient macrophages about 10-fold less efficiently t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(49 citation statements)
references
References 52 publications
4
45
0
Order By: Relevance
“…The HIV strains inhibited included those using both CCR5 and CXCR4 coreceptors (2028), those using CXCR4 alone (2044 and IIIB) or those using CCR5 alone (SF162 and BaL). With the exception of IIIB, all can infect both macrophages as well as CD4 + T cells [43]. These data support a target upstream of viral fusion events (or upstream of those fusion events involving HIV coreceptors).…”
Section: Discussionmentioning
confidence: 53%
“…The HIV strains inhibited included those using both CCR5 and CXCR4 coreceptors (2028), those using CXCR4 alone (2044 and IIIB) or those using CCR5 alone (SF162 and BaL). With the exception of IIIB, all can infect both macrophages as well as CD4 + T cells [43]. These data support a target upstream of viral fusion events (or upstream of those fusion events involving HIV coreceptors).…”
Section: Discussionmentioning
confidence: 53%
“…Whereas AMD2763 was found to inhibit HIV replication in various human T cells at a concentration of 0.14Ϫ1.4 M [96], AMD3100 inhibited HIV replication within the nanomole range [97]. The inhibitory effects of AMD3100 on X4 HIV-1 strains have been demonstrated in a wide variety of cells expressing CXCR4, including PBMCs, and, vice versa, various X4, R5/X4 but not R5 HIV-1 viruses have proven sensitive to AMD3100 in PBMCs and M/M [99,[101][102][103]. Recently, a follow-up drug has been reported.…”
Section: Targeting the Hiv Coreceptorsmentioning
confidence: 99%
“…Others, however, utilise only CXCR4 for entry yet infect macrophages efficiently (9). We and others have found that such strains infect D32D32 CCR5 macrophages and that this infection can be inhibited by specific ligands to CXCR4 (33)(34)(35). Thus, both CCR5 and CXCR4 act as functional co-receptors on primary macrophages.…”
Section: Co-receptors As Determinants Of Cell Tropism and Pathogenesismentioning
confidence: 85%
“…We have shown that multi-co-receptor-using isolates rely predominantly on CCR5 for macrophage infection (33). The reduced level of infection by such strains in D32D32 CCR5 macrophages is completely inhibited by ligands to CXCR4.…”
Section: Role Of Alternative Co-receptors In Vivomentioning
confidence: 90%
See 1 more Smart Citation